Population density of Arabica coffee cultivars for bean quality and yield - Carvalho Silveira, Jane Maria de; Nasser, Mauricio Dominguez; Carvalho Mariano-Nasser, Flavia Aparecida de [UNESP]; Pagliarini, Maximiliano Kawahata; Giomo, Gerson Silva (Univ Federal Goias, 2018)
For the implantation of a coffee tree crop, aiming at a high yield, each cultivar, depending on the plant distribution and density, can express differently its results. This study aimed to evaluate the yield potential and grain quality of Arabica coffee cultivars grown under different spacings between rows and between plants. A randomized block design was used, with three replications, in a split-split-plot scheme, being the plots three coffee cultivars (Obata IAC-1669-20, Tupi IAC-1669-33 and Catuai Vermelho IAC-144), four spacings between rows (1.8 m, 2.0 m, 2.5 m and 3.0 m) and four spacings between plants in the row (0.5 m, 0.7 m, 0.8 m and 1.0 m), totaling 48 treatments. The type of coffee bean (flat, peaberry and elephant) and yield per hectare were evaluated. The Obata cultivar showed the highest potential yield, in relation to Tupi and Catuai Vermelho, and also the highest percentage of flat grains. The factors, in order of importance, that interfere with the potential yield of processed coffee are the cultivar and the spacing between rows and between plants.